2017
DOI: 10.3389/fncir.2017.00103
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Population Activity in Spinal Motor Circuits: Greater Than the Sum of Its Parts

Abstract: The core elements of stereotypical movements such as locomotion, scratching and breathing are generated by networks in the lower brainstem and the spinal cord. Ensemble activities in spinal motor networks had until recently been merely a black box, but with the emergence of ultra-thin Silicon multi-electrode technology it was possible to reveal the spiking activity of larger parts of the network. A series of experiments revealed unexpected features of spinal networks, such as multiple spiking regimes and logno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…In a recent study, Petersen and Berg ( 2016 ) demonstrated that the firing rate of populations of neurons from the turtle spinal cord is normally distributed on a log-scale (lognormal) (see also Berg, 2017 ). We examined whether the firing rate before and after the onset of movement for the extensor, intermediate, and flexor interneurons is also lognormally distributed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Petersen and Berg ( 2016 ) demonstrated that the firing rate of populations of neurons from the turtle spinal cord is normally distributed on a log-scale (lognormal) (see also Berg, 2017 ). We examined whether the firing rate before and after the onset of movement for the extensor, intermediate, and flexor interneurons is also lognormally distributed.…”
Section: Resultsmentioning
confidence: 99%
“…The studies performed by Petersen and Berg ( 2016 ) contribute to our understanding of the spinal circuitry responsible for scratching in a new perspective. These authors demonstrated for the first time that the behavior of neural populations in the spinal cord could not be properly described by the mean and standard deviation of their firing rate (Berg, 2017 ). They found that the firing rate of spinal neurons during different forms of scratching is lognormally distributed (Petersen and Berg, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, shunting ipsilateral inhibition might serve to enforce tight temporal control over spike timing via shortening membrane time constants. Alternatively or in addition, ipsilateral inhibition might function as a form of gain control to prevent saturation, analogous to somatic inhibition in hippocampus and cortex [11, 63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is widespread in the central nervous system, and there is evidence that neurons interact through phase resetting to establish a time frame for information encoding and decoding (Canavier, 2015), among other behaviors. In particular, the analysis of phase resetting is of interest in circuits known as central pattern generators (CPGs) because the elucidation of their structure and organization is a work in progress and because the cooperation between CPGs is poorly understood (Berg et al, 2007; Stuart and Hultborn, 2008; McCrea and Rybak, 2008; Harris-Warrick, 2010; Enriquez-Denton et al, 2012; Tsuruyama et al, 2013; Grillner and El Manira, 2015; Kiehn, 2016; Ramirez et al, 2016; Pujala et al, 2016; Berg, 2017; Stein, 2018; Steuer and Guertin, 2019).…”
Section: Introductionmentioning
confidence: 99%